1) x^2 - 13x + 42 = 0
To solve this, you have to ask yourself: what two numbers multiply to make 42 (the third constant term) and add to make -13 (the coefficient of x)? The answer to that is -6 and -7, so this factors as
(x - 6)(x - 7) = 0
In order for this to equal 0, x - 6 = 0 or x - 7 = 0. Solving these two equations, we get x = 6 or x = 7.
2) x^2 - 8x - 65 = 0
What two numbers multiply to make -65 and add to make -8? The answer to that is -13 and +5, so this factors as
(x - 13)(x + 5) = 0
Which means x = 13 or x = -5.
2007-02-02 08:26:33
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
x^2-13x+42=0 = (x-7)(x-6) = x=7 & x=6
x^2-8x-65=0 = (x-13)(x+5) = x=13 & x= -5
thats easy all u have 2 do is get da factors 4 da third number and make sure u can get da 2nd number as plus or minus da way it is in da equations
2007-02-02 17:15:23
·
answer #2
·
answered by elektra 1
·
0⤊
0⤋
factoring
1st one
x^2 - 13 x + 42 = 0
to
(x - 7)(x - 6) = 0
so x = 7 or x = 6
and the second
x^2 - 8 x - 65 = 0
(x - 13)(x+5)
so x = 13 or x = -5
2007-02-02 16:28:28
·
answer #3
·
answered by dhaval70 2
·
0⤊
0⤋
use the quadratic formula x = { -b +/- sqrt(b^2-4ac)}/2a
x^2 -13x +42 =0
x = (13 +/- sqrt{13^2-4*42})/2
x = (13 +/- sqrt{1})/2
x=12/2 =6 and x=14/2=7
x^2-8x-65
x=(8 +/-sqrt{64+4*65})/2
x=(8 +/- sqrt{324})/2)
x=(8 +/- 18)/2
x=26/2 = 13 and x = 10/2 = 5
2007-02-02 16:50:56
·
answer #4
·
answered by bignose68 4
·
0⤊
0⤋
lol...
1st equation ~ x=7 , x=6
2nd equation ~ x=13 , -5
2007-02-02 16:32:55
·
answer #5
·
answered by uzairsml 1
·
0⤊
0⤋
Isn't that the point in homework?
If someone else does it for you, then you might as well quit school.
2007-02-02 16:24:30
·
answer #6
·
answered by superfunkmasta 4
·
1⤊
0⤋
do your own homework!!! its a friday and I dont do homework on fridays, especially not other peoples.
2007-02-02 16:29:02
·
answer #7
·
answered by flutterflie04 5
·
0⤊
0⤋
i would say go to http://www.studybuddy.com . Its the best!
2007-02-02 16:29:27
·
answer #8
·
answered by The Kwl Kid 3
·
0⤊
0⤋